2016
DOI: 10.1002/1873-3468.12079
|View full text |Cite
|
Sign up to set email alerts
|

MRP1 mediates folate transport and antifolate sensitivity in Plasmodium falciparum

Abstract: Edited by Ned ManteiMultidrug resistance-associated proteins (MRP) of Plasmodium falciparum have been associated with altered drug sensitivity. Knowledge on MRP substrate specificity is indispensible for the characterization of resistance mechanisms and identifying its physiological roles. An untargeted metabolomics approach detected decreased folate concentrations in red blood cells infected with schizont stage parasites lacking expression of MRP1. Furthermore, a tenfold decrease in sensitivity toward the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…None of the Peruvian samples presented mutations on pfk13, pfatg18, pfarps10 and ferredoxin that have been associated with artemisinin resistance 45 , 46 nor pfexo which is associated with piperaquine 47 nor pfmrp1 which is associated with sulfadoxine/pyrimethamine and artemether/lumefantrine resistance 48 .…”
Section: Resultsmentioning
confidence: 91%
“…None of the Peruvian samples presented mutations on pfk13, pfatg18, pfarps10 and ferredoxin that have been associated with artemisinin resistance 45 , 46 nor pfexo which is associated with piperaquine 47 nor pfmrp1 which is associated with sulfadoxine/pyrimethamine and artemether/lumefantrine resistance 48 .…”
Section: Resultsmentioning
confidence: 91%
“…Increased expression of pfmrp1 gene has been associated with mefloquine, quinine, and chloroquine resistance. Moreover, this protein has been reported to be involved in the export of folate from malaria parasites into red blood cells [20]. The P. falciparum multidrug resistance gene 1 ( pfmdr1 ) that encodes a P-glycoprotein homologue is also located on the membrane of parasite digestive vacuole, the main target of action of most antimalarial drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a 10 fold increase in methotrexate (MTX) IC 50 response was documented in parallel (190-1800 nM). In a subsequent experiment, adding folate to the medium (10 fold, towards 23 nM) further increased the parasite resistance to MTX (less then 2 fold, IC 50 2700 nM), attesting for the influence of the intracellular pool status (Rijpma et al, 2016a). Data concerning the other antifolate drugs were unfortunately not reported, albeit a similar de-sensitization outcome is expectable.…”
Section: The Folate Pool Factormentioning
confidence: 91%
“…Whatever pf MRP1 and pf MRP2 roles are in P. falciparum physiology, they can be dispensable for the intra-erythocytic cycle. Gene editing experiments have shown that the full deletion of pfmrp1 in W2 ( Raj et al, 2009 ) and NF-54 (the strain from which 3D7 clone was obtained) ( Rijpma et al, 2016 ; Rijpma et al, 2016 ), as well as the pfmrp2 ablation in the latter, renders viable parasites—at least at in vitro conditions, and with these particular clones.…”
Section: Pf Mrp S —Potential Natural Roles In the Parasite Physiologymentioning
confidence: 99%
See 1 more Smart Citation